The role of CD1a-restricted T cells and phospholipase in allergic disease - Subramaniam, S (2015)
The skin is an important barrier against a range of different environmental challenges. The skin associated immune system is able to detect breaks in the barrier to initiate a protective immune response. Langerhans cells express a high density of CD1a, which presents lipid antigens to T-cells. However little is known about CD1a-restricted lipid antigens and the role of CD1a-restricted T-cells in inflammatory skin disease. In order to investigate the role of T-cells that react to CD1a presenting lipid in skin disease, wasp and bee venom were studied as an antigen source. Venoms are able to cause allergic hypersensitivity reactions, associated with skin T-cell infiltration, a venom protein-specific T-cell response in allergic individuals and are independent of filaggrin. Using primary antigen presenting cells and target cells lacking surface MHC expression (K562 cells) transfected with CD1a, allowed investigation of polyclonal T-cells responses from unrelated donors. Bee and wasp venoms were shown to induce CD1a-restricted T-cell responses in both peripheral blood and skin. Surprisingly this activity was not contained within the lipid fraction of the venoms, but instead was mediated through the generation of a lipid ligand by venom phospholipase. Furthermore, wasp venom delivery results in the production of phospholipase products in the skin of humans. A significantly increased frequency of IFN-, GM-CSF- and IL-13-producing venom specific CD1a-restricted T-cells was observed in allergic individuals compared to healthy controls. During subcutaneous immunotherapy, frequencies of CD1a-reactive T cells were initially induced, peaking by weeks 5, but then reduced despite escalation of antigen dose. CD1a-reactive T cells were further investigated to characterise their physiological role by generating T cell lines which produced a range of different cytokines, including IL-22 on stimulation with phospholipase and other phospholipase containing allergens. In summary, we identified a novel pathway of skin inflammation where lipids generated by allergen-derived phospholipase can be recognised by CD1a-restricted T cells which produce type 1 and type 2 cytokines and associate with allergic reactivity. These findings have implications for novel therapeutic strategies for allergic disease.